(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Allergic rhinitis and rhinosinusitis are among the most common inflammatory diseases of the upper respiratory tract and frequently coexist in clinical practice. Chronic inflammation of the nasal mucosa caused by allergic mechanisms may contribute to impaired sinus drainage, mucociliary dysfunction, and increased susceptibility to infectious rhinosinusitis. Understanding the pathophysiological relationship between these conditions is essential for selecting effective treatment strategies. This article reviews current data on the interaction between allergic rhinitis and rhinosinusitis, clinical features of comorbidity, and modern therapeutic approaches aimed at controlling inflammation and preventing disease progression.